Short- and long-term effects of transarterial chemoembolization on portal hypertension in patients with hepatocellular carcinoma. Issue 6 (July 2019) - Scheiner, Bernhard; Ulbrich, Gregor; Mandorfer, Mattias; Reiberger, Thomas; Müller, Christian; Waneck, Fredrik; Trauner, Michael; Kölblinger, Claus; Ferlitsch, Arnulf; Sieghart, Wolfgang; Peck-Radosavljevic, Markus; Pinter, Matthias
Background: Transarterial chemoembolization (TACE) affects hepatic perfusion, and might have an impact on portal pressure in patients with hepatocellular carcinoma (HCC). Objective: The objective of this article is to report the secondary outcome "hepatic hemodynamics" from the AVATACE trial, a prospective randomized, placebo-controlled trial on the efficacy of conventional TACE in combination with bevacizumab or placebo. Methods: Hepatic venous pressure gradient (HVPG) was measured at baseline (prior to first TACE), within nine days ("acute effects"), two months ("intermediate effects") and six months ("long-term effects") after the first TACE. Results: Of 28 patients with early-intermediate stage HCC, n = 20 (71%) had clinically significant portal hypertension (CSPH, HVPG ≥ 10 mmHg) at baseline (median, 12 (interquartile range (IQR): 9–19) mmHg). TACE had neither "acute effects" nor "intermediate effects" on HVPG. However, in 13 patients with available HVPG measurement at month 6, there was a significant increase in HVPG (median, 16 (IQR: 11–19) mmHg) compared with baseline (median, 10 (IQR: 5–12) mmHg; p = 0.007). Portal hypertension-related complications occurred exclusively in patients with CSPH (8 (40%) vs 0). Conclusions: Repeated TACE was associated with a significant long-term increase in HVPG. This should be considered when deciding whether to continue with TACE or switch to systemic treatment, since CSPH drives the development of complications.